Pengaruh Media Pembelajaran Berbantuan Wordwall terhadap Hasil Belajar Siswa Matematika Kelas IV SDN 173633 Porsea - Graldo Immanuel Siagian; Daitin Tarigan (Journal on Education, 2023)
Now days, the use of technology can be used as an interactive learning medium. Interactive learning media are tools/objects that can provide convenience and can support the successful implementation of learning, because learning media can facilitate students' understanding in receiving learning because through these technological media students can easily access and receive messages for learning mathematics or other learningThe research was carried out with the of knowing effect of learning media Wordwall on learning outcomes of fourth grade mathematics students. This type of research uses an experimental method of quasi-experimental design with a pretest-posttest Nonequivalent control group design. The data analysis technique used was the normality and homogeneity tests of Shapiro Wilk and used paired sample t-test with the help of SPSS 24 for Windows. Based on the results of post-test calculations before using Wordwall assisted learning media, students' pretest scores obtained an average score of 39.79 which changed after being treated to 79.37 after using the media. From the results of the study it can be concluded that wordwall learning media has an influence on the learning outcomes of fourth grade mathematics students.